Legionella effector LpPIP recruits protein phosphatase 1 to the mitochondria to induce dephosphorylation of outer membrane proteins. - Kai-Qi Yek; Evie R Hodgson; Ching-Seng Ang; Catherine S Palmer; Ann E Frazier; Hayley J Newton; Diana Stojanovski (PLoS Biology, 2025)
Legionella pneumophila utilizes a type IVB secretion system (T4SS) to translocate over 300 effector proteins into host cells, hijacking cellular processes, including those within the mitochondrion. Currently, no Legionella effectors have been identified at the mitochondrial outer membrane, a critical interface between the organelle and the rest of the cell. We screened the Legionella effector repertoire for features of mitochondrial tail-anchored (TA) proteins and identified four putative TA effectors. Among them, LpPIP (Lpg1625) localizes to the mitochondrial outer membrane and interacts with all three isoforms of protein phosphatase 1 (PP1) via an RVxF motif, functioning as a PP1-interacting protein (PIP). Importantly, PP1 remains catalytically active upon interaction with LpPIP to dephosphorylate mitochondrial outer membrane proteins. Altering the TA signature to direct LpPIP to the ER induces ER-recruitment of PP1 and dephosphorylation of ER-resident proteins, indicating that LpPIP controls PP1 localization and not substrate specificity. This study uncovers a novel pathogen-mediated strategy to modulate PP1 and manipulate the host cell phosphoproteome.